2014
DOI: 10.1038/npp.2014.114
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Chiari I Malformation in Children of Mothers with Depression with and without Prenatal SSRI Exposure

Abstract: Selective serotonin reuptake inhibitors (SSRIs) are frequently prescribed to pregnant women. Therefore, research on in utero exposure to SSRIs can be helpful in informing patients and clinicians. The aim of this retrospective two-cohort study was to determine whether there is a statistically significant increase in Chiari I malformations (CIM) in children exposed to SSRIs during pregnancy. A total of 33 children whose mothers received a diagnosis of depression and took SSRIs during pregnancy (SSRI-exposed coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Participants were drawn from three prospective longitudinal neuroimaging studies being carried out at UNC (Gilmore et al, 2010; Gilmore et al, 2012; Knickmeyer et al, 2014). Recruitment occurred through community physicians, relevant clinics at UNC, including the perinatal psychiatry clinic and general obstetrics clinics, and mass emails to the UNC community.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were drawn from three prospective longitudinal neuroimaging studies being carried out at UNC (Gilmore et al, 2010; Gilmore et al, 2012; Knickmeyer et al, 2014). Recruitment occurred through community physicians, relevant clinics at UNC, including the perinatal psychiatry clinic and general obstetrics clinics, and mass emails to the UNC community.…”
Section: Methodsmentioning
confidence: 99%
“…One study reported benign caudothalamic cysts in 6 of 40 at term infants exposed to SSRIs but no unexposed comparison group was evaluated (Laine et al, 2003). We recently reported that children exposed to SSRIs prenatally exhibit a striking increase in Chiari I malformations, a condition resulting from the underdevelopment of the posterior cranial fossa and overcrowding of the normally developing hindbrain (Knickmeyer et al, 2014). The current study is the first to examine brain tissue volumes and white matter development of SSRI-exposed neonates.…”
Section: Introductionmentioning
confidence: 99%
“…Human brain imaging studies show that functional network activity underlies the typical cognitive and behavioral processes reportedly altered by PME, and that aberrant connectivity is linked to atypical functional development in other disorders (Bressler and Menon, 2010 ; Insel, 2010 ). A small number of research groups have begun to document how and when these functional networks develop in typical neonates (Lin et al, 2008 ; Gao et al, 2009 ; Fransson et al, 2013 ), and have shown that prenatal exposure to other psychoactive drugs alters early structure (Grewen et al, 2014 ; Knickmeyer et al, 2014 ) and connectivity (Salzwedel et al, 2015 ). Animal studies show prenatal THC-induced disruption of neural connectivity that results in long-lasting alterations in structure and function of cortical circuitry (Tortoriello et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the included studies point to a linkage between SSRIs and ASD, with almost all published studies pointing to increases in risk even if in individual studies the increase is not significant [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83].…”
Section: Resultsmentioning
confidence: 99%